Advances in Human Factors in Simulation and Modeling Proceedings of the AHFE 2017 International Conference on Human Factors in Simulation and Modeling, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA (Advances in Intelligent Systems and Computing,, 2018)
This book focuses on computational modeling and simulation research that advances the current state-of-the-art regarding human factors in simulation and applied digital human modeling. It reports on cutting-edge simulators such as virtual and augmented reality, on multisensory environments, and on modeling and simulation methods used in various applications, such as surgery, military operations, occupational safety, sports training, education, transportation and robotics. Based on the AHFE 2017 International Conference on Human Factors in Simulation and Modeling, held on July 17-21, 2017, in Los Angeles, California, USA, the book is intended as a timely reference guide for researchers and practitioners developing new modeling and simulation tools for analyzing or improving human performance. It also offers a unique resource for modelers seeking insights into human factors research and more feasible and reliable computational tools to foster advances in this exciting research field.